Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) Varietas Bima Brebes Akibat Dosis PGPR Akar Bambu - Noertjahyani, Noertjahyani; Roosma Ria, Elly; Romiyadi; Nurul Hanati, Ayu (OrchidAgro, 2024)
Shallots are vegetable commodities whose economic value and needs are quite high in the country, this has caused a decrease in the value of shallot exports over the last 5 years. Therefore, it is necessary to increase shallot production in order to increase the export value of shallots again by using Plant Growth Promoting Rhizobacteria (PGPR) biological fertilizers containing good microorganisms that can produce phytohormones, help increase soil fertility and reduce pests. The research was conducted in the experimental land of the Faculty of Agriculture, Winaya Mukti University, Sumedang Regency. The research implementation time is from February 2023 to August 2023. The purpose of this study was to determine the effect of growth and yield of onion plants and obtain the best dose of bamboo root PGPR on the yield of onion plants of the Bima Brebes variety. The environmental design uses Group Random Design (RAK) consisting of 5 treatments (A = 0 L ha-1, B = 2 L ha-1, C = 4 L ha-1, D = 6 L ha-1, E = 8 L ha-1) and repeated 5 times. The results showed that the dose of PGPR bamboo roots had a significant effect on the yield of onion plants of the Bima Brebes variety on the observation parameters of the number of tubers per clump, the number of tubers per plot and the fresh weight of tubers per clump. No dose of bamboo root PGPR gave the best results, but one dose of PGPR showed better results at a dose of 6 L Ha-1 on observation of the number of tubers per plot.Keywords: Shallot, Bima Brebes, Dose, PGPRShallots are vegetable commodities whose economic value and needs are quite high in the country, this has caused a decrease in the value of shallot exports over the last 5 years. Therefore, it is necessary to increase shallot production in order to increase the export value of shallots again by using Plant Growth Promoting Rhizobacteria (PGPR) biological fertilizers containing good microorganisms that can produce phytohormones, help increase soil fertility and reduce pests. The research was conducted in the experimental land of the Faculty of Agriculture, Winaya Mukti University, Sumedang Regency. The research implementation time is from February 2023 to August 2023. The purpose of this study was to determine the effect of growth and yield of onion plants and obtain the best dose of bamboo root PGPR on the yield of onion plants of the Bima Brebes variety. The environmental design uses Group Random Design (RAK) consisting of 5 treatments (A = 0 L ha-1, B = 2 L ha-1, C = 4 L ha-1, D = 6 L ha-1, E = 8 L ha-1) and repeated 5 times. The results showed that the dose of PGPR bamboo roots had a significant effect on the yield of onion plants of the Bima Brebes variety on the observation parameters of the number of tubers per clump, the number of tubers per plot and the fresh weight of tubers per clump. No dose of bamboo root PGPR gave the best results, but one dose of PGPR showed better results at a dose of 6 L Ha-1 on observation of the number of tubers per plot.Keywords: Shallot, Bima Brebes, Dose, PGPRShallots are vegetable commodities whose economic value and needs are quite high in the country, this has caused a decrease in the value of shallot exports over the last 5 years. Therefore, it is necessary to increase shallot production in order to increase the export value of shallots again by using Plant Growth Promoting Rhizobacteria (PGPR) biological fertilizers containing good microorganisms that can produce phytohormones, help increase soil fertility and reduce pests. The research was conducted in the experimental land of the Faculty of Agriculture, Winaya Mukti University, Sumedang Regency. The research implementation time is from February 2023 to August 2023. The purpose of this study was to determine the effect of growth and yield of onion plants and obtain the best dose of bamboo root PGPR on the yield of onion plants of the Bima Brebes variety. The environmental design uses Group Random Design (RAK) consisting of 5 treatments (A = 0 L ha-1, B = 2 L ha-1, C = 4 L ha-1, D = 6 L ha-1, E = 8 L ha-1) and repeated 5 times. The results showed that the dose of PGPR bamboo roots had a significant effect on the yield of onion plants of the Bima Brebes variety on the observation parameters of the number of tubers per clump, the number of tubers per plot and the fresh weight of tubers per clump. No dose of bamboo root PGPR gave the best results, but one dose of PGPR showed better results at a dose of 6 L Ha-1 on observation of the number of tubers per plot.Keywords: Shallot, Bima Brebes, Dose, PGPR